Effect of Simulated Gastrointestinal Conditions on Biofilm Formation by Salmonella 1, 4, [5], 12:i:-. (30th June 2014) - Seixas, R.; Gabriel, M.; Machado, J.; Tavares, L.; Bernardo, F.; Oliveira, M.
Abstract : Salmonella Typhimurium 1, 4, [5], 12:i:- is a major serovar responsible for human salmonellosis whose biofilm-forming ability, influenced by environmental conditions like those found in the gastrointestinal tract, is one of the main contributing factors to its ability to persist in the host and thus one of the main causes of chronic relapsing infections. Most studies to evaluate biofilm formation are performed in microtiter assays using standard media. However, no reports are available on the ability of this serovar to produce biofilm under in vitro simulated gastrointestinal conditions which better correlate with the environment found in the gastrointestinal tract. To address this, a modified biofilm assay simulating intestinal fluid was conceived to assess the biofilm formation of 133 Salmonella Typhimurium 1, 4, [5], 12:i:- isolates with and without agitation and at three different time points (24 h, 48 h, and 72 h). The results were then compared to the existing microtiter method using conventional biofilm growth medium (Mueller Hinton Broth). Statistical analysis revealed significant differences in the results obtained between the three protocols used. The simulated human intestinal environment impaired biofilm production demonstrating that conditions like pH, agitation or the presence of enzymes can influence biofilm production. Therefore, results from in vitro simulation of in vivo conditions may contribute to unravelling factors relating to biofilm formation and persistence in the context of the human host.